Age-Related Preservation of Trust Following Minor Transgressions. (14th October 2016) - Bailey, Phoebe E; Petridis, Katherine; McLennan, Skye N; Ruffman, Ted; Rendell, Peter G
Abstract: Objectives: This study assesses age-related differences in the weighting and integration of appearance and behavior cues to trustworthiness. The aim is to assess whether it becomes more difficult with age to detect a cheater in disguise. Method: Young and older adults invested real money in a repeated trust game with trustees who varied on facial expression (smiling, neutral, angry) and return rate (high, low). Trustees were also rated for trustworthiness pre- and post-trust game. Results: Young and older adults learned to disregard appearances to invest more in trustees providing high relative to low returns. Both groups also updated ratings of trustworthiness from pre- to post-trust game in the direction of behavior that was incongruent with appearance. Notably, young (but not older) adults updated ratings of smiling trustees with a high return rate (i.e., returned money on 8 of 10 investments) to reflect reduced trustworthiness in line with the 2 instances of cheating from those trustees. Discussion: The findings show that there are no age-related differences in the way that obvious cheating in disguise is punished with reduced trustworthiness ratings. However, older adults are less vigilant to more subtle cheating in disguise, or are more forgiving of transgressions perceived as minor.